MODELLING OF FLUID FLOW AND CUTTINGS TRANSPORT IN HORIZONTAL NARROW ANNULI IN THE PRESENCE OF PIPE ROTATION - OFEI, TITUS NTOW (2016)
The motivation for this research originated from the lack of understanding on the mechanisms of fluid flow and cuttings transport in horizontal narrow annular drilling such as casing-while-drilling (CwD). Both concentric and eccentric annular geometries with diameter ratios, K, from 0.64 to 0.90 and pipe rotation speeds from 0 rpm to 300 rpm were considered. The study adopted numerical and analytical approaches to achieving its objectives.